FRI0095 Subclinical Hypothyroidism is Associated with an Increased Risk of Cardiovascular Events in Patients with Rheumatoid Arthritis. (9th June 2015) - Agca, R.; Raterman, H.G.; Simsek, S.; Voskuyl, A.E.; Nurmohamed, M.T.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an increased risk of developing cardiovascular disease (CVD). This risk is only partially explained by classic risk factors for CVD. Autoimmune thyroid disease often coexists with RA and has been associated with an elevated cardiovascular (CV) risk, especially in hypothyroid patients. However, the existing studies show conflicting results. Objectives: To investigate whether patients with thyroid dysfunction at baseline have an increased incidence of CVD compared to euthyroid RA patients. Methods: In this study thyroid function was assessed in 353 RA patients participating in an ongoing prospective cohort study to assess cardiovascular morbidity and mortality (CARRΈ study). Cardiovascular end points were defined as a verified medical history of coronary, cerebral or peripheral arterial disease. Cox regression analyses were performed to calculate hazard rates (HR) and to adjust for confounders. Results: The participants were predominantly females (65.7%) with a mean age of 63±6 years and a mean disease duration of 8±4 years. At baseline 4.6% was hypothyroid, 4.0% was hyperthyroid, 2.6% had subclinical hyperthyroidism and 2.9% had subclinical hypothyroidism. 85.9% of the patients was euthyroid. In the total population 58 patients (16.4%) had developed CVD after 5 years of follow up. Compared with euthyroid patients crude HR were 1.20 (95%CI 0.37 – 3.89; P=0.76) for hyperthyroid patients, 0.83 (95% CI 0.20 – 3.43; P=0.80) for hypothyroid patients, 0.59 (95%CI 0.89 – 5.92; P=0.61) for subclinical hyperthyroidism and 2.30 (95%CI 0.89-5.92; P=0.084) for subclinical hypothyroidism. Intriguingly, only subclinical hypothyroidism was associated with incident CVD compared to euthyroid patients in the adjusted models. The age and gender adjusted HR for CV events in this group was 3.36 (95% CI 1.29 – 8.77; P=0.013). The HR was 3.85 (95% CI 1.45 – 10.19; P=0.007) after adjustment for prevalent CVD and metabolic syndrome. The final model corrected for RA duration, and disease activity showed a HR of 3.23 (95% CI 1.09 – 9.58; P=0.035). Conclusions: Coexistence of subclinical hypothyroidism with RA was associated with incident CVD. If external validation can confirm this amplified CVD risk, thyroxine supplementation and cardiovascular risk management may be warranted in this subgroup of patients. Disclosure of Interest: None declared